Comparative evaluation of the effect of two pulpal medicaments on pain and bleeding status of mandibular molars with irreversible pulpitis post-failure of inferior alveolar nerve block: a double-blind, randomized, clinical trial - Singh,Naomi Ranjan; Mishra,Lora; Pawar,Ajinkya M.; Kurniawati,Nike; Wahjuningrum,Dian Agustin (PeerJ, 2022)
Background Complete relief of pain due to irreversible pulpitis is challenging to obtain with analgesic medications. The high incidence of an inferior alveolar nerve block (IANB) failure makes it difficult for practitioners to perform endodontic treatment without implementing other anesthetic techniques, especially mandibular molars. The aim of this study was to compare efficacies of two different quantities of paraformaldehyde based pulpal medicaments to relieve the pain and control hyperemic pulp post-failure of IANB and supplementary technique in patients experiencing this symptomatic irreversible pulpitis in the permanent mandibular tooth. Method Eighty-two participants with severe pain pre-operatively (Heft Parker Visual Analogue Scale, VAS > 114 mm) were enrolled, and pain responses were recorded at different time intervals using the Heft Parker visual analogue scale. To the patients experiencing pain even after the administration of the standard IANB and supplemental intraligamentary injection, one of the two paraformaldehyde based pulpal medicaments was placed in the pulp chamber and sealed. Participants were recalled after 24–48 h (second visit) to assess pain and bleeding reduction. Results Results showed a significant decrease in pain severity and bleeding score post medicament placement (p < .05). Hence judicious use within a recommended period, pulpal medicaments can be considered safe. Conclusion Paraformaldehyde based pulpal medicament can be used as an alternative to manage pain in patients having severe irreversible pulpitis and hyperalgesia.
Keywords: Hyperalgesia; Inferior alveolar nerve block; Irreversible pulpitis; Paraformaldehyde; Visual analogue scale